Bilirubin–Albumin Binding and Free Bilirubin - Ahlfors, Charles E (Journal of perinatology, 2001)
The relevance of plasma bilirubin-albumin binding and, in particular, the nonalbumin-bound or "free" bilirubin concentration to neonatal bilirubin toxicity is controversial. The pivotal role that "free" bilirubin played in the bilirubin toxicity that occurred following administration of sulfisoxazole or benzyl alcohol to jaundiced newborns, and the correlation of "free" bilirubin with bilirubin-induced changes in the auditory brainstem response are strong support for measuring "free" bilirubin when evaluating neonatal jaundice. Reliable methods for measuring "free bilirubin" are available, and population reference values are needed to help determine its proper clinical use.